PENGARUH ORIENTASI KEWIRAUSAHAAN DAN INOVASI PRODUK TERHADAP KEUNGGULAN BERSAING (Studi Kasus pada Sentra Susu Lembang) - Iva Yustisia (JURISMA : Jurnal Riset Bisnis & Manajemen, 2016)
The Effect Of Entrepreneurial Orientation and Product Innovation To Competitive Advantages (Study Case on Sentra Susu Lembang), under the guidance of Dr. Dwi Raeni Santy. SE., M.Si In running a business course, companies are required to be able to produce a quality product that can be consumed by any among consumers , of course, produce a quality product will affect the competition . Where to produce a quality product means it can gain a competitive advantage .This study aims to determine Entrepreneurial Orientation, Product InnovationÂ  that influences on the Competitive Advantages in the Industrial Center of milk Lembang partially and simultaneously.The method that is used in this research is descriptive method verification. The unit of analysis in this study is Entrepreneurs who are in the Industrial Center of milk Lembang Government in total 35 entrepreneurs. The test statistic that is used is the calculation of Pearson correlation, path analysis, the coefficient of determination, hypothesis testing, where the testing is done using the help of IBM SPSS application program 20 for Windows Lisrel.The results showed that Entrepreneurial Orientation in the are in the Industrial Center of milk Lembang significantly Product Innovation as independent variables and Competitive Advantages as dependent variables. In correlation calculations showed a strong relationship between Entrepreneurial Orientation with the Competitive Advantages. Entrepreneurial Orientation and the Competitive Advantages have a positive correlation, means that if Entrepreneurial Orientation is good, it will increase Competitive Advantages to be achieved by the Industrial Center of milk Lembang, if the that Entrepreneurial Orientation is not good, it will decrease the Competitive Advantages in the the Industrial Center of milk Lembang.